MINERAL DEVICED FROM FINE CLAY ISOLATED FROM POTTER WASP NEST COLLECTED FROM UNIVERSITI TEKNOLOGI PETRONAS MAIN HALL - ABU SAMAH, MUHAMAD ASRI (2011)
THIS PROJECT IS MAINLY ABOUT RESEARCHING AND EXPERIMENT ON A CLAY USE BY AN INSECT TO BUILD THEIR NEST. THIS REPORT WILL REPRESENT IN DETAILS ON THE INTRODUCTION ABOUT THE PROJECT WHICH IS TO BRIEFLY ABOUT THE STUDY, THE PROBLEM STATEMENT, THE OBJECTIVES AND METHODOLOGY USED IN CONDUCTING THE EXPERIMENT.